2020
DOI: 10.1002/cre2.292
|View full text |Cite
|
Sign up to set email alerts
|

Retracted publications and their citation in dental literature: A systematic review

Abstract: Objectives The present systematic review aimed to perform an in‐depth analysis of the different features of retracted publications in the dental field. Material and methods This review has been recorded in the PROSPERO database (CRD42017075634). Two independent reviewers performed an electronic search (Pubmed, Retraction Watch) for retracted articles in dental literature up to December 31, 2018. Results 180 retracted papers were identified, the first published in 2001. Retractions increased by 47% in the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 49 publications
7
32
0
Order By: Relevance
“…Tumor Biology and Molecular Biology Reports retracted the largest number of studies; these results were similar to those identi ed in other studies [5,[23][24][25][26][27][28][29][30] . SRs involving research misconduct (especially authorship issues and fraudulent peerreview) took longer to retract than research with honest errors, which was also observed in previous studies [23][24][25][31][32][33][34] .…”
Section: Discussionsupporting
confidence: 70%
“…Tumor Biology and Molecular Biology Reports retracted the largest number of studies; these results were similar to those identi ed in other studies [5,[23][24][25][26][27][28][29][30] . SRs involving research misconduct (especially authorship issues and fraudulent peerreview) took longer to retract than research with honest errors, which was also observed in previous studies [23][24][25][31][32][33][34] .…”
Section: Discussionsupporting
confidence: 70%
“…Due to the rapid development of the COVID-19 pandemic and the short publication timeframe, some published articles have subsequently been retracted or rejected and replaced with newer information. The publication of unreliable papers has several negative consequences that can increase the chance of incorrect treatment for patients [30]. In this study, an attempt was made to use more valid and practical articles and protocols.…”
Section: Post Dental Treatmentmentioning
confidence: 99%
“…According to Bozzo et al ( 2017 ), 61% of cancer publications were retracted due to academic misconduct: plagiarism, duplicate publication, and fraud. Rapani et al ( 2020 ) found that almost 28% of retracted dental literature was contributed by Indian authors. Faggion Jr et al ( 2018 ) found that nearly 57% of retracted dental literature was published between 2012 and 2016.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A troubling trend is the rising number of retracted scientific papers (Fang and Casadevall 2011 ). Very recently, Rapani et al ( 2020 ) found that India was the top country in the retracted publications in the dental literature with about 28% and India was one among the top five countries in the retractions (Bhatt 2020 ; Tang et al 2020 ). These are the motivation behind this study.…”
Section: Introductionmentioning
confidence: 99%